2022
DOI: 10.1115/1.4055500
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling and Cold Streaks Tracking on a Fully Cooled Nozzle Guide Vane Under Representative Combustor Outflow Conditions

Abstract: The pronounced non uniform temperature distribution in the core engine flow path is a recurring problem of gas turbine engine design process, as it directly affects turbine performance and lifetime. Specifically, turbine entry conditions are usually characterised by severe temperature distortions, often referred to as hot and cold streaks. Temperature distortions remain an issue even at the exit section of the NGV, with additional cold streaks coming from the vane cooling system. Various studies focus on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several activities were performed in a test rig designed by Cubeda et al [79] (see Section 3.2.1) to analyze the redistribution of the hot flow in the cooled vane passage in the presence of a strong residual swirl. Babazzi et al [80] used Pressure-Sensitive Paint (PSP) to evaluate film cooling performance and an oxygen concentration probe to track cold streak migration, and demonstrated that in the investigated configuration, low-coverage areas appeared on the suction side due to swirl-induced alterations of the streamlines. The presence of a strong residual swirl modified the stagnation line shape and position, thus altering vane load distribution [80] and the heat transfer coefficient maps [81].…”
Section: Residual Swirl On Turbine Inlet Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several activities were performed in a test rig designed by Cubeda et al [79] (see Section 3.2.1) to analyze the redistribution of the hot flow in the cooled vane passage in the presence of a strong residual swirl. Babazzi et al [80] used Pressure-Sensitive Paint (PSP) to evaluate film cooling performance and an oxygen concentration probe to track cold streak migration, and demonstrated that in the investigated configuration, low-coverage areas appeared on the suction side due to swirl-induced alterations of the streamlines. The presence of a strong residual swirl modified the stagnation line shape and position, thus altering vane load distribution [80] and the heat transfer coefficient maps [81].…”
Section: Residual Swirl On Turbine Inlet Sectionmentioning
confidence: 99%
“…Babazzi et al [80] used Pressure-Sensitive Paint (PSP) to evaluate film cooling performance and an oxygen concentration probe to track cold streak migration, and demonstrated that in the investigated configuration, low-coverage areas appeared on the suction side due to swirl-induced alterations of the streamlines. The presence of a strong residual swirl modified the stagnation line shape and position, thus altering vane load distribution [80] and the heat transfer coefficient maps [81]. Moreover, the unsteady nature of the swirling flow generated a fluctuating map of adiabatic effectiveness that was not represented by the time-averaged one.…”
Section: Residual Swirl On Turbine Inlet Sectionmentioning
confidence: 99%